Effectiveness of Inductive Thinking Model in Teaching Science of VIII Class Students in terms of their Achievement - Tiwari, Surendra Kumar; Yadav, Prabha (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
The research paper is based on “effectiveness of inductive thinking model in teaching science of viii class students in terms of their achievement, “the study is Experimental in nature where one group Pre- test post-test design were used. The purposive Sampling Technique was used for collection of data. The sample consists of 44 male and female students of VIII class from Indore City. the researcher had developed lesson plans in Science from NCERT syllabus based on Inductive Thinking Model. The Achievement test was developed by the researcher which consists of 25 multiple choice questions of Science, for assessing Intelligence Raven‟s Standard Progressive Matrices was used.  Correlated T test and two-way ANOVA was used to analyze the data. It was found that Inductive Thinking Model was effective in terms of Achievement in Science of VIII class Students. Key words: Inductive Thinking Model, Achievement, Science.